Israeli Ethno-Religious Differences in Motherhood Penalties on Employment and Earnings. Issue 2 (April 2023) - Budig, Michelle J.; Kraus, Vered; Levanon, Asaf
Israeli society presents a unique context for studying motherhood's impacts on employment and earnings: High fertility and marriage rates coincide with high rates of women's education and employment. While past research finds low motherhood penalties in Israel, ethno-religious group differences in these penalties are unexplored. Ours is the first longitudinal study to examine simultaneously motherhood's employment and wage penalties among Israeli ethno-religious groups. Using newly available panel data, we find that motherhood deters employment among Israeli-Palestinians more strongly than among Jews, and particularly among less-educated Israeli-Palestinians. Similarly, motherhood wage penalties and ethno-religious disparities are greatest among the least-educated women. For all groups, highly educated women incur smaller motherhood penalties in employment and earnings, and in some cases receive motherhood wage premiums. Public-sector employment, particularly for Muslims, is associated with higher postnatal employment, lower motherhood penalties, and motherhood premiums among the highly educated. The stronger enforcement of anti-discrimination and work–family policies in the public sector, along with its schoolteachers' collective bargaining agreement that raises maternal earnings, may contribute to its more positive outcomes for Israeli-Palestinian mothers. Our findings suggest that increasing educational attainment and public-sector employment among Israeli-Palestinians may reduce ethno-religious inequality in motherhood's impact on employment and earnings.